A Therapeutic Silencing RNA Targeting Hepatocyte TAZ Prevents and Reverses Fibrosis in Nonalcoholic Steatohepatitis in Mice. Issue 9 (23rd July 2019) - Wang, Xiaobo; Sommerfeld, Mark R.; Jahn‐Hofmann, Kerstin; Cai, Bishuang; Filliol, Aveline; Remotti, Helen E.; Schwabe, Robert F.; Kannt, Aimo; Tabas, Ira
Abstract : Nonalcoholic steatohepatitis (NASH) is emerging as a major public health issue and is associated with significant liver‐related morbidity and mortality. At present, there are no approved drug therapies for NASH. The transcriptional coactivator with PDZ‐binding motif (TAZ; encoded by WW domain‐containing transcription regulator 1 [ WWTR1 ]) is up‐regulated in hepatocytes in NASH liver from humans and has been shown to causally promote inflammation and fibrosis in mouse models of NASH. As a preclinical test of targeting hepatocyte TAZ to treat NASH, we injected stabilized TAZ small interfering RNA (siRNA) bearing the hepatocyte‐specific ligand N‐acetylgalactosamine (GalNAc‐siTAZ) into mice with dietary‐induced NASH. As a preventative regimen, GalNAc‐siTAZ inhibited inflammation, hepatocellular injury, and the expression of profibrogenic mediators, accompanied by decreased progression from steatosis to NASH. When administered to mice with established NASH, GalNAc‐siTAZ partially reversed hepatic inflammation, injury, and fibrosis. Conclusion : Hepatocyte‐targeted siTAZ is potentially a novel and clinically feasible treatment for NASH. Abstract : This study demonstrates in a preclinical model that silencing hepatocyte TAZ using a platform shown so far to be safe and effective in humans can both block steatosis‐to‐NASH progression and help reverse features of already established NASH. The importance of further work in this area is underscored by the fact that NASH is emerging worldwide as the leading cause of liver transplantation and hepatocellular carcinoma and that no drugs are currently approved to treat this devastating illness.